Thermal cracking of effective decontamination and recycling of lubricating oil: mechanisms, conditions, and performance enhancements - Nafeena Abdul Munaf R; Senthil Kumar Kandasamy; Bakkiyaraj M; Dheeraj Kumar Gara; Abdul Munaf A (Materials Research Express)
Thermal cracking of SAE 40 lube oil contamination is a critical process for maintaining the efficiency and longevity of industrial machinery and automotive engines. This study investigates the mechanisms and outcomes of thermal cracking as a method to decompose and remove contaminants from lube oil (SAE40) and investigates the possibility of the use of solid coke produced as residue after the cracking process. The research also examines the optimal conditions for thermal cracking, including temperature ranges, heating rates, and the influence of catalysts. Analytical techniques such as thermogravimetry (TGA), Fourier-transform infrared spectroscopy (FTIR), and thermograms (DSC) are employed to characterize the chemical composition of the solid produced after treatment. This result reveals that the produced coke after the treatment demonstrates the resin capability, and it can be used as a binder or additive in lower temperature applications. This study underscores the potential of thermal cracking as an effective method for recycling contaminated lube oil, thereby contributing to sustainability and cost-efficiency in industrial maintenance practices.